The Scope and Limitations of Incorporating Externalities in Competition Analysis within a Consumer Welfare Approach - Roman Inderst; Stefan Thomas (ZBW – Leibniz Information Centre for Economics, 2021)
The failure to fully internalize externalities from production and consumption, including on future generations, is supposed to be at the core of the perceived failure to ensure (ecological) sustainability within the realm of antitrust enforcement. As policymakers put increasing pressure on competition agencies to account for sustainability in their enforcement practice, it becomes pivotal to define whether and, if so, how such externalities can be incorporated into competition analysis. Rather than positing that sustainability should constitute a goal in itself, we explore how sustainability can be incorporated within a consumer welfare analysis. Our paper makes a key distinction between what we term an individualistic and a collective consumer welfare analysis. Within an individualistic consumer welfare analysis, consumers' willingness-to-pay is measured ceteris paribus, holding other consumers' choices fixed. We explore how, e.g., through contingent valuation and conjoint analysis, consumers' appreciation of sustainability benefits and with it the reduction of externalities on others can be elicited. Specifically, we discuss how the context-sensitivity of extracted willingness-to-pay provides both challenges and opportunities for antitrust enforcement in the context of sustainability measures. In a collective consumer welfare analysis, consumers may express their willingness-to-pay also for the choices of others and, thereby, also for the reduction of externalities on themselves. Borrowing from environmental and resource economics, we also discuss more indirect ways of incorporating such externalities. And we critically assess the possibility of "laundering" consumers' sustainability preferences in the light of supposed biases and cognitive limitations.
Keywords: A13; K21; K32; 330; sustainability; externalities; willingness-to-pay